Model Infiltrasi Das Suatu Tinjauan Perbandingan Metodologi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
ABSTRACT: Infiltration is one of the hydrologic sub models, and it plays an important role in the hydrologic cycle. By knowing the rate and amount of infiltration, the volume of runoff can be calculated. The aims of this paper to provide an insight of cachtment infiltration models, especially that of methodology comparison. The models which will be reviewed are simple, empirical ones, and time-dependent infiltration models, namely Horton, Kostiakov, and Philip models. Data on infiltration rate are measured using a Double-Ring infiltrometer. The determination of the best predictive model is by fitting process, which can be done by the use of infiltration curves, using small increments of time. The Horton and Kostiakov models fit well with the experimental data In this case, Horton model fits better than Kostiakov's. Philip model predicts a too low infiltration rate. All of the models use empirical parameters or constants, therefore, in using these models in the field, the constants should be adjusted to the local condition.